FAO commodity review and outlook. 1975-1976 - FAO (Rome : Food and Agriculture Organisation, 1976)
Highlights and analyses world market developments affecting agricultural, fishery and forestry products.
lje 14/06/2017
Loans
Keywords: Agriculture--Economic aspects; Produce trade; Agricultural industries; Primary commodities; Commercial products